(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
OWC-type wave power devices are widely used around the world due to their stable operating conditions. Therefore, most of the commercially operated wave power plants are OWC-type. The energy conversion devices of OWC-type wave power plants can be broadly categorized into OWC chamber, air turbine, and generator. The power performance evaluation of the power plant through real-sea operation is based on the electrical power relative to the input flux according to IEC TS / 62600-100. However, it is not easy to evaluate the efficiency of each energy conversion step. This paper evaluated the real- sea performance of the OWC chamber and air turbine of an OWC-type wave power plant operating in the real sea. The physical values measured in the wave power plant operating in the real sea are the pressure in the chamber, the rpm of the turbine, and the electrical output of the generator. In this study, a physical model was developed to evaluate the performance of each energy conversion stage of a wave power plant operating in the real sea area. Using the developed physical model, the efficiency of each energy conversion stage of the wave power plant was evaluated. Then, the efficiency of the OWC chamber and air turbine of the wave power plant was evaluated in connection with the actual measurement data. Finally, comparative verification was performed with real- sea operation results.